Traces of Islamic Sovereignty in Eastern Europe in the Middle Ages - Johan Septian Putra; Karali, Nurcan (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2022)
Islam once gained sovereignty in the Eastern European region, which constituted the majority of Christians before Islam and after Islam entered there. In this contemporary era, Islam is not the majority place in Europe from the west to the east. The existence of Islam in the region in this modern era is inseparable from the historical contributions of the two axes of medieval Islamic dynasties, namely the Golden Horde Dynasty and the Ottoman Empire. The research objectives of this article are to describe the geographical location of Eastern Europe, explain the early arrivals, and analyze the two axes of Islamic sovereignty in medieval Eastern Europe. The research method of this study is a historical research method with library research and tracing information sources for this study through the internet. The flow or procedure of the historical research method includes four stages: heuristics, source criticism, interpretation, and historiography. The results of this study explain that ideological political factors are the most core factors in determining countries to enter Eastern Europe and the two nations that contributed to the existence of Islamic sovereignty in Eastern Europe in the Middle Ages were the Mongols from 1235 to 1557 AD and the Turks from 1365 to 1574 AD through raids and conquests against Christian kingdoms in the region.